PEMANFAATAN WEARABLE DEVICES DALAM PEMANTAUAN PASIEN DIABETES MELLITUS TIPE 2 DI INDONESIA: SCOPING REVIEW - Akri, Yusnita Julyarni; Adelia, Donna Dwinita; Yunamawan L.S, Donny; Irawan, Yanuar Hadi (Forind Press, 2025)
Type 2 diabetes mellitus (DMT2) is one of the chronic diseases with a high prevalence in Indonesia. The main challenges in patients are limited self-monitoring, low adherence to therapy, and early detection of complications. Wearable devices, such as smartwatches and health sensors, are starting to be used globally to monitor the condition of DMT2 patients, but the evidence of their use in Indonesia is still not comprehensively mapped. Identify and map the literature related to the use of wearable devices in monitoring DMT2 patients in Indonesia. This study is a scoping review that follows the framework of the Arksey & O'Malley methodology. Literature searches were conducted on PubMed, Scopus, ScienceDirect, Google Scholar, and Garuda with a range of 2013–2025. Keywords include